HAKIKAT ‘IRFĀN - Sayyed Hosseini Kouhsari; Muhammad Nur (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2013)
‘Irfān or Sufism is defined as the knowledge of God or ma‘rifa al-Ḥaqq. Theoretically and practically, it is a discipline that originated in the Islamic tradition from Islam itself and has its roots in the Qur’an and ḥadiths of the Prophet Muhammad. This statement at the same time rejects some orientalists who however maintained the view that ‘irfān and tasawuf and its subtle and sublime ideas have come into the Islamic world from outside, which is non-Islamic origins.